Eleocharis pedrovianae, a new species of Cyperaceae from Northern Brazil (Serra dos Carajás, Pará State) - Nunes, Clebiana De Sá; Gil, André Dos Santos Bragança; Trevisan, Rafael (Phytotaxa, 2016)
Eleocharis pedrovianae is a new species of Cyperaceae from the Serra dos Carajás (Pará State, Brazil), herein described and illustrated. This species lives as a submerged herb in wetlands, marshes and margins of temporary lakes and lagoons with ferric soil (canga). It is morphologically similar to Eleocharis angustispicula, differing by its stoloniferous stem system, the presence of chasmogamous basal spikelets, a perianth of 4(5) bristles, an ellipsoid achene, and a stylopodium that is brown pyramidal, and separated from the achene body by a constriction.